Program Fisioterapi Pada Kondisi Low Back Pain Et Causa Ischialgia - Trisnandhika Galang Pratama; Umi Budi Rahayu (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Low back pain is pain that occurs in the lower spine, especially in the lumbar vertebrae region, low back pain is one of the causes of disability in people under 45 years of age, this condition causes limitations in the body's functional activities so that it affects the patient's quality of life (Ripollés -Melchor et al., 2022). One of the causes of low back pain, one of which is the presence of nerve clamping in the lumbar segment or commonly known as ischialgia. Ischialgia is a manifestation of low back pain that occurs due to clamping of the sciatic nerve, causing paraesthesia/tingling along the journey of the sciatic nerve root, this is one of the causes of low back pain (Rini & Rakasiwi, 2021). Objective: This study aims to determine the effect of providing physiotherapy interventions in the form of Short Wave Diathermy (SWD), Transcutaneous Electrical Nerve Stimulation (TENS), myofascial release, stretching and strengthening exercises in reducing pain intensity, increasing joint range of motion and increasing muscle strength. Methods: a case report study conducted at the Condong Catur Hospital, Jogjakarta on patients Mr. S aged 64 years, this study was conducted directly on the respondent by giving therapy for 3 times. The results were a decrease in pain intensity, an increase in ROM, an increase in muscle strength and an increase in functional ability and activity. Conclusion: a comprehensive physiotherapy program in cases of low back pain et causa ischialgia was proven to be able to reduce pain intensity, increase ROM, increase muscle strength and increase functional ability and activity. Keywords: Low back pain, ischialgia, Short Wave Diathermy (SWD), Transcutaneous Electrical Nerve Stimulation (TENS), myofascial release, stretching, strengthening exercise